Gestão escolar e formação de professores em modelagem matemática na educação matemática: um olhar - Bellei, Patrick (2018)
Mathematical Modeling is one of the trends in mathematics education that is more strengthened, considering the large number of researchers who are dedicated to the theme and the increasing formation of groups or research lines. Even with this strengthening its use in the classroom is still embryonic. In papers published on this topic in events related to mathematics education, it is possible to find notes that refer to the necessity of specific training, empowering teachers for this purpose, as well as sparse indications about the difficulty of approximation with the modeling as a result of the school management. These aspects and others are objects of the project for the extension of continuous education of teachers in Mathematical Modeling in mathematics education that is configured as our region of investigation. This formation occurs in Foz do Iguaçu2 under a mixed model, in an approximation to the established by Garcia (1999). While taking part in this training, in addition to the contributions of the research group, it was possible to verify in the speech of participants that the school management can influence the use of this trend. In this broader context of research, the training itself, along with my interests as a researcher, the question emerges: what is shown about the school management in relation to the mathematical modeling from the participating teachers of continuous education?, guiding this research, which has been developed under a phenomenological perspective. To proceed with the questioning, we not only looked at the school management, but for the meaning attributed by the participating teachers training at the school organization as a reflection of the school management. The survey data were collected from audio recordings of the speech of participants, resulting of the meetings of continuous formation from November 2015 to August 2016, which were transcribed. Therefore, this research sought the meaning given in the discourse through its significance considering the hermeneutics, using Atlas.ti software. because it is a powerful tool for the analysis of large amount of qualitative data. Initially were highlighted the meaning units, which after an analysis converged into three open categories that have been described, being they: about the influences of the school management in the method of work and differentiated activities; on the school organization, planning and external assessments; and on the role of manager at school for teachers. The research shows, among other things, the need of support and knowledge of school management to the activities of Mathematical Modeling and actions for the development of continuous training. It also shows the importance that the school management has clear objectives and defined in conjunction with all professionals so that the differentiated activities as the mathematical modeling may provide significant education for the critical training of students.